Determinants Of Customer Satisfaction Against The Intention To Revisit At Hangry Fast Food Restaurant - Kustianti, Nia Nur; Chairun Nisa, Puspita (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2024)
In Liu and Jang's (2009) research, they state that revisit intentions are important because the company's focus on its mission and goals can be maintained by reviewing revisit intentions, which ensures that all actions and decisions are in line with these intentions. The purpose of this study is to explore the influence of food quality, perceived value, fair price, customer satisfaction, revisit intentions, and Electronic of Mouth. The population of this study is people who live in Jakarta, Bogor, Depok, Tanggerang, and Bekasi who order Hangry online. The sample in this study was 160 people. Using a nonpurposive sampling method to select respondent criteria. The data analysis method used is path analysis through the Partial Least Squares Structural Equation Model (PLS-SEM). In this study it was found that food quality has an effect on fair price, fair price and food quality has an effect on perceived value. Food quality, fair price, and perceived value do not affect customer satisfaction. Customer satisfaction influences revisit intention. Customer satisfaction did not successfully influence E-WOM.